If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 42 = -1x + 7x + -12 Reorder the terms: 42 = -12 + -1x + 7x Combine like terms: -1x + 7x = 6x 42 = -12 + 6x Solving 42 = -12 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 42 + -6x = -12 + 6x + -6x Combine like terms: 6x + -6x = 0 42 + -6x = -12 + 0 42 + -6x = -12 Add '-42' to each side of the equation. 42 + -42 + -6x = -12 + -42 Combine like terms: 42 + -42 = 0 0 + -6x = -12 + -42 -6x = -12 + -42 Combine like terms: -12 + -42 = -54 -6x = -54 Divide each side by '-6'. x = 9 Simplifying x = 9
| 174=68-x | | -3+5x=-7+1+6x-1 | | -80=-0.16x | | -y+125=191 | | -80=-0.16 | | 7(-3p+4)-5p=28 | | 192-v=3 | | -1.08+0.92= | | (5*x-3)+4=3 | | -5(6m-7)=5 | | 4(-3n+1)=64 | | -8x+30=62 | | 7(x+7)=7 | | X^3-225=0 | | log(4)(x)+log(8)(x^2)=3 | | 0.6r=-78 | | 8(7x-1)=-8 | | 10x+70=90 | | 5-6(x-3)=10 | | 11x+21=142 | | -2m-7=2m+5 | | (x^6)-(x^3)-(6)=0 | | -3(6+5k)-k=-34 | | 5(a+4)-6(4c^2+6-9a)= | | 3y+z=13 | | 3(2x+2)=9x+3-3x+3 | | l=ol | | x+90+x+90+x=360 | | -8a+5a=12 | | lo=l | | 180+4n=360 | | .75x^2-.25x=.50 |